Analisis Kajian Feminisme dalam Cerpen Pemetik Air Mata Karya Agus Noor - Feny Arta Melinda; Annisa Riski Arista; Nadila Putri Nirwana; Muhammad Isman (FKIP, Universitas Palangka Raya, 2025)
Feminist literary criticism is one of the literary criticisms that seeks to describe and examine women's experiences in various literary works. This study aims to describe women's struggles in facing gender injustice and seeking freedom in a patriarchal society. The main character, who is a woman, shows courage and determination in the face of social norms that limit her role and rights as a female individual. There is this study the author uses a structural approach. The structural approach aims to explain as carefully as possible the functions and relationships between literary works and show the relationship between these elements. The research used in this study is a qualitative descriptive method. The data in this study is in the form of feminist literary criticism in a short story entitled Tear Picker by Agus Noor, which is contained in a collection of short stories by Agus Noor. Conclusion: 1) in a short story Pemetik Air Mata by Agus Noor which tells how women are treated, where lies the self-esteem of a woman who should get a decent life not only limited to satisfying the needs of men. 2) there are three schools of feminism contained in Agus Noor's short story Pemetik Air Mata, namely Social Feminism, Marxist Feminism, and Social Liberal.